Mitochondrial Fission and Fusion: Molecular Mechanisms, Biological Functions, and Related Disorders - Mode Al Ojaimi; Azza Salah; Ayman W. El-Hattab (Membranes, 2022)
Mitochondria are dynamic organelles that undergo fusion and fission. These active processes occur continuously and simultaneously and are mediated by nuclear-DNA-encoded proteins that act on mitochondrial membranes. The balance between fusion and fission determines the mitochondrial morphology and adapts it to the metabolic needs of the cells. Therefore, these two processes are crucial to optimize mitochondrial function and its bioenergetics abilities. Defects in mitochondrial proteins involved in fission and fusion due to pathogenic variants in the genes encoding them result in disruption of the equilibrium between fission and fusion, leading to a group of mitochondrial diseases termed disorders of mitochondrial dynamics. In this review, the molecular mechanisms and biological functions of mitochondrial fusion and fission are first discussed. Then, mitochondrial disorders caused by defects in fission and fusion are summarized, including disorders related to MFN2, MSTO1, OPA1, YME1L1, FBXL4, DNM1L, and MFF genes.